Discussion of Total Actuarial Liabilities and Normal Costs - Putri Zahra, Ami Emelia (Operations Research: International Conference Series, 2021)
Many company owners are still confused about calculating pensions for their employees so that company owners cannot prepare pensions properly. In this discussion, we will discuss the problem of calculating the total actuarial obligations and normal costs that are part of the pension fund. The purpose of this discussion is to show the solution to the problem of how to find total liabilities using the ordinary credit unit method and to find normal costs using the projected credit unit method. The calculation of total actuarial liabilities uses the credit unit method, while the normal cost calculation discussed uses the projected unit credit actuarial cost method. From the problems discussed, the total actuarial liability on 1/1/95 was IDR 405,335,428 and the normal cost for 1994 on 1/1/94 was IDR 1,071,429. The purpose of this discussion is to help readers better understand how to complete the calculation of total actuarial obligations and normal costs and can be a reference for readers in determining the amount of costs prepared for pensions.